Hur påverkas utbildade vårdhundar (Canis lupus familiaris) av sitt arbete inom humanvården? - Ehrén, Elin (2014)
Today therapy dogs (Canis lupus familiaris) service people more than ever and different categories of work places use therapy dogs to help their caretakers. Many studies have been made on the positive effects in patients when they are given contact with a dog, but very little have been done on how the dog experience its situation and what kind of behaviour a therapy dog shows during its working days.